2019
DOI: 10.1038/s41598-019-55208-5
|View full text |Cite
|
Sign up to set email alerts
|

MAP2K1 is a potential therapeutic target in erlotinib resistant head and neck squamous cell carcinoma

Abstract: Epidermal growth factor receptor (EGFR) targeted therapies have shown limited efficacy in head and neck squamous cell carcinoma (HNSCC) patients despite its overexpression. Identifying molecular mechanisms associated with acquired resistance to EGFR-TKIs such as erlotinib remains an unmet need and a therapeutic challenge. In this study, we employed an integrated multi-omics approach to delineate mechanisms associated with acquired resistance to erlotinib by carrying out whole exome sequencing, quantitative pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 74 publications
(73 reference statements)
1
6
0
Order By: Relevance
“…Accordingly, pathway analysis indicated that the targets of each herb in YWLS were enriched in these signaling pathways. We found that increased expression of 42 genes was associated with decreased survival, which was consistent with previous evidence, such as EGFR, AKT1, SERPINE1, HSP90AA1, HSP90B1 (Fan et al, 2020), PLAU (Li et al, 2021), MAP2K1 (Jain et al, 2019), and CCND1 (Feng et al, 2011). Among these survival-related genes, 33 genes had higher expression in tumor tissues than in normal tissues like EGFR, AKT1, and HSP family genes, suggesting they could serve as diagnostic markers to distinguish normal from tumoral samples.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Accordingly, pathway analysis indicated that the targets of each herb in YWLS were enriched in these signaling pathways. We found that increased expression of 42 genes was associated with decreased survival, which was consistent with previous evidence, such as EGFR, AKT1, SERPINE1, HSP90AA1, HSP90B1 (Fan et al, 2020), PLAU (Li et al, 2021), MAP2K1 (Jain et al, 2019), and CCND1 (Feng et al, 2011). Among these survival-related genes, 33 genes had higher expression in tumor tissues than in normal tissues like EGFR, AKT1, and HSP family genes, suggesting they could serve as diagnostic markers to distinguish normal from tumoral samples.…”
Section: Discussionsupporting
confidence: 90%
“…Dual inhibition of EGFR and MAPK/CDK4/6 prevented oesophageal squamous cell carcinoma (OSCC) progression (Zhou et al, 2017). Therapeutic targeting of MAP2K1 in the MAPK pathway was a promising strategy for EGFR inhibitor (erlotinib)-resistant HNSCC patients (Jain et al, 2019). It was reported that Aurora kinases were potential targets to overcome EGFR inhibitor resistance in HNSCC, indicating that Aurora kinase A (AURKA) blockade might be a promising approach (Kim and Bandyopadhyay, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It thereby inhibits receptor autophosphorylation and blocks downstream signals 16 . Erlotinib is used in treatment of different types of cancer as lung cancer 17 and head and neck squamous cell carcinoma 18 . Many studies showed beneficial effects of erlotinib in different kidney injuries.…”
Section: Introductionmentioning
confidence: 99%
“…EMT is a dynamic change in cellular architecture that leads to changes in cell migration and invasion. Its role has been well documented in developmental process and closely associated with tumor dissemination and metastasis [ 43 , 44 ]. Several genetic, epigenetic, and proteomic regulators are known to coordinate this highly complex process.…”
Section: Discussionmentioning
confidence: 99%